The giver - Lowry, Lois. (Boston : Houghton Mifflin, 1993)
Given his lifetime assignment at the Ceremony of Twelve, Jonas becomes the receiver of memories shared by only one other in his community and discovers the terrible truth about the society in which he lives.
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
Book Links (A.L.A.), May 2004.
Booklist starred, April 1993.
Elem. School Library Collection, June 2000.
Keywords: Science fiction; Newbery Medal; Science fiction